Forms of Muslim self-perception in European Islam - Brunner, Rainer (Hagar: Studies in Society and Culture, 2005)
The growing importance of Islam in Western Europe has led to an intense discussion among Muslims on their position vis-a-vis Islamic values and the secular Western social order. Three examples have been chosen to illustrate this debate. While the Mufti of Marseille, Soheib Bencheikh, argues in favor of Muslims adopting the French concept of laicite, the Swiss intellectual Tariq Ramadan makes a European Muslim identity dependent on preservation of traditional legal prescriptions. Finally, the Central Council of Muslims in Germany has issued a charter aimed at reflecting Muslim attitudes towards Western society.